Pendampingan Pendidikan Anak di Era Digital pada PKK Desa Krumpakan - Sri Jumini; Hamzah Hamzah; Desty Putri Hanifah; Deni Aryati; Taufan Jannata (Yayasan Keluarga Guru Mandiri, 2024)
The increasingly rapid development of technology requires parents and education administrators to be more creative in managing children's education. Technological sophistication in various brands and types of cell phones has captured the world of children so that they no longer play games involving their peers. The effect is low emotional maturity, children tend to be selfish, don't socialize easily, are addicted to games, decreased achievement, promiscuity, and decreased achievement. Capturing and observing this, the UNSIQ team carried out activities to assist children's education in the digital era. This service activity was carried out by PKK women from Krumpakan Village, Kajoran subdistrict, Magelang Regency, totaling 40 members. Seeing the positive response and enthusiasm of the participants in taking part in this training, shown by the attendance percentage of 90%, it is hoped that it will become a routine village program. The impact of this activity is that participants understand how education should be implemented in the family, how to respond to children who are addicted to gadgets, and its influence on children's emotional maturity, so that juvenile delinquency, brawls, drug abuse, promiscuity, and the impact of the digital era can be prevented and controlled early on.